Biologically Active Compositions Containing Neurotrophic Factors Change the Contractile Activity of Detrusor of Rats with Infravesical Obstruction - Globa, Vyacheslav; Bondarenko, Tatyana; Bozhok, Galina; Samburg, Yana; Legach , Evgen (Problems of Cryobiology and Cryomedicine, 2020)
The contractile activity of urinary bladder (UB) after introduction of biologically active compositions (BAC) containing neurotrophic factors in female rats with infravesical obstruction, which was modeled by a ligature to the urinary tract distal part, was investigated. Cryoextract of the spinal ganglia (SG), conditioned culture media of native and cryopreserved mantle gliocytes (MG), the bulk medium, the drug "Cortexin" were used as BAC. Animals were injected with BAC for 10 days and the contractile activity (CA) of isolated UB strips was determined by measuring KCl-induced and agonist-dependent responses. The use of BAC, in addition to Cortexin, contributed to the CA restoration. The conditioned culture medium of cryopreserved MG and cryoextract of SG increased the agonist-dependent response by 4.6 and 2.5 times, respectively, compared to the CA of the control animals. The rats in these groups showed the highest indices of maximal amplitude of contraction, similar to the control ones. Probl Cryobiol Cryomed 2020; 30(2): 188-198